Application of image processing software for ribeye steak marbling assessment and its correlations with beef quality attributes - Mahasawasde, Supparin; Khejornsart, Pichad; Wiwatthanapornchai, Sitthinan (Agriculture and Natural Resources, 2025)
Importance of Work: Image processing software (IPS) provides a promising method for improving ribeye steak marbling assessment, having a strong correlation with intramuscular fat content (IMF). Objectives: To evaluate ribeye steak marbling using IPS and to investigate correlations between image-derived data and beef quality attributes: color, texture, IMF and carnosine content (CC). Materials and Methods: Ribeye steak was sampled from four cattle breeds: Wagyu (Wi), Wagyu crossbreed (Wx), Angus (Ai) and Angus crossbreed (Ax). Digital sample images were captured and marbling quantification was conducted using IPS and expressed as fat area (FA). Correlations were investigated between image-derived data using IPS and other attributes. Results: IPS identified color differences between Ai and Ax and illustrated similarities between Wi and Wx based on colorimetry data. The IPS displayed better color variation in muscle and IMF than the colorimeter. The IPS successfully applied FA to show marbling differences between Ai and Ax and between Wi and Wx, with the results being the same as from using the IMF results. Ai had softer texture and higher CC than Ax; however, these values did not differ for Wi and Wx. FA, calculated based on IPS, had strong correlations with IMF and CC; however, FA had no significant correlation with hardness. Main Findings: IPS demonstrated its potential in a marbling evaluation tool for ribeye steaks based on IMF and CC estimations. Digital image capture and IPS were more efficient at evaluating sample color than the standard colorimetry method. IPS should be feasible in beef quality prediction and marbling scale development in the meat slaughter industry